2002
DOI: 10.1159/000057317
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Signals from Receptor Tyrosine Kinases and G Protein-Coupled Receptors

Abstract: Activation of G protein-coupled receptors (GPCRs) leads to stimulation of classical G protein signaling pathways. In addition, GPCRs can activate the mitogen-activated protein kinases (MAPKs) such as the extracellular signal-regulated kinases, c-Jun NH2-terminal kinases (JNKs), and p38 MAPKs, and thereby influence cell proliferation, cell differentiation and mitogenesis. Cross talk between GPCRs and receptor tyrosine kinases (RTKs) is an incredibly complex process, and the exact signaling molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(96 citation statements)
references
References 113 publications
2
93
0
1
Order By: Relevance
“…Probably, Hoey is dealing with the so-called transactivation of growth factors tyrosine kinase (TK) receptors by PTHrP G-protein-coupled receptor (GPCR) (Linseman et al, 1995;Lowes et al, 2002). We observed a similar phenomenon in 2002 while culturing skin fibroblasts in the presence of serum (then of growth factors) .…”
Section: Sirmentioning
confidence: 68%
“…Probably, Hoey is dealing with the so-called transactivation of growth factors tyrosine kinase (TK) receptors by PTHrP G-protein-coupled receptor (GPCR) (Linseman et al, 1995;Lowes et al, 2002). We observed a similar phenomenon in 2002 while culturing skin fibroblasts in the presence of serum (then of growth factors) .…”
Section: Sirmentioning
confidence: 68%
“…Several studies have found that GPCRs transactivate RTKs that exert neurotrophic effects, such as the insulin growth factor (IGF)-1 receptor, EGFR, and TrkA/B [37][38][39] . PF has been studied for decades and has many effects in vivo and in vitro, several of which are independent of A 1 R [3,20] .…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that CDS is monitoring appropriate cellular physiological changes, as it is known that PTK and GPCR signaling pathways overlap and that similar cellular physiological outputs will manifest from stimulation of members of each of these families. [29][30][31][32][33] within a receptor family, different receptors of the same class tend to produce the same kinds of patterns, whereas receptors of different classes produce different patterns. However, patterns produced from receptors of 2 different families may be similar due to the convergent nature of the physiological responses elicited.…”
Section: Arrow) Hela Cell Patterns (A-d) Cho Cell Patterns (E F)mentioning
confidence: 99%